Lipomatous variant of angiomyofibroblastoma: a case report and review of the literature. (9th January 2015) - Upreti, Sheela; Morine, Angela; Ng, Daniel; Bigby, Susan M.
Abstract : Angiomyofibroblastoma represents a rare, benign mesenchymal tumor with a predilection for the vulvovaginal region. Lipomatous change may occur but rarely comprises a substantial component of the lesion. There are only eight reports in the English language literature describing the lipomatous variant of this tumor. We describe a further lipomatous angiomyofibroblastoma that occurred on the labium majus of a 49‐year‐old woman. The histopathologic and immunohistochemical features are described, and the collective experience in the literature is reviewed.